Metabolic effects of Lactobacillus reuteri DSM 17938 in people with type 2 diabetes: A randomized controlled trial. Issue 4 (7th February 2017) - Mobini, Reza; Tremaroli, Valentina; Ståhlman, Marcus; Karlsson, Fredrik; Levin, Max; Ljungberg, Maria; Sohlin, Maja; Bertéus Forslund, Heléne; Perkins, Rosie; Bäckhed, Fredrik; Jansson, Per‐Anders
Abstract : Aims: To investigate the metabolic effects of 12‐week oral supplementation with Lactobacillus reuteri DSM 17938 in patients with type 2 diabetes on insulin therapy. Materials and methods: In a double‐blind trial, we randomized 46 people with type 2 diabetes to placebo or a low (10 8  CFU/d) or high dose (10 10  CFU/d) of L. reuteri DSM 17938 for 12 weeks. The primary endpoint was the effect of supplementation on glycated haemoglobin (HbA1c). Secondary endpoints were insulin sensitivity (assessed by glucose clamp), liver fat content, body composition, body fat distribution, faecal microbiota composition and serum bile acids. Results: Supplementation with L. reuteri DSM 17938 for 12 weeks did not affect HbA1c, liver steatosis, adiposity or microbiota composition. Participants who received the highest dose of L. reuteri exhibited increases in insulin sensitivity index (ISI) and serum levels of the secondary bile acid deoxycholic acid (DCA) compared with baseline, but these differences were not significant in the between‐group analyses. Post hoc analysis showed that participants who responded with increased ISI after L. reuteri supplementation had higher microbial diversity at baseline, and increased serum levels of DCA after supplementation. In addition, increases in DCA levels correlated with improvement in insulin sensitivity in the probiotic recipients. Conclusions: Intake of L. reuteri DSM 17938 for 12 weeks did not affect HbA1c in people with type 2 diabetes on insulin therapy; however, L. reuteri improved insulin sensitivity in a subset of participants and we propose that high diversity of the gut microbiota at baseline may be important.